Digital Learning Management as a Catalyst for Quality Education - Asiah Ratu Sesma; Bukman Lian; Muhammad Juliansyah Putra (Journal of Social Work and Science Education, 2026)
This study aims to analyze the implementation of digital learning management specifically its planning, implementation, and evaluation in improving learning quality at MAN 3 Palembang. Employing a qualitative approach with a case study design, the research involved subjects including the head of the madrasah, curriculum vice principal, teachers, IT operators, students, supervisors, and parents. Data were collected through in-depth interviews, participatory observation, and documentation studies, analyzed using an interactive model with triangulation for validity. The findings reveal that digital learning management has been implemented systematically. Planning involves digital-based lesson design and strengthening teachers' digital competencies, supported by adequate infrastructure. Implementation utilizes Learning Management Systems (LMS), Google Classroom, interactive digital media, and technology-based assessments. Evaluation comprises formative and summative assessments, serving as a foundation for continuous improvement. The novelty of this study lies in its comprehensive, multi-stakeholder perspective on digital learning management within an Indonesian madrasah context, moving beyond mere technological availability to examine holistic management processes. Practically, it provides a replicable framework for educational institutions seeking to enhance learning quality through structured digital integration. The study contributes to educational management literature by offering empirical evidence that systematic digital learning management encompassing planning, implementation, and evaluation positively impacts learning quality in secondary Islamic education settings.